THE SIMULATION ROLE IN CONTEMPORARY DENTAL MEDICINE - Norina Forna; Hans Christoph Lauer (Romanian Dental Association for Education, 2015)
The computerized programs have an unquestionable role in attaining high educational standards. Besides, they are efficient tools to identify the clinical case particularities as well as to evaluate them in accordance with the sum of clinico-biological indices specific to the clinical case. During the didactic process, the simulation has an essential role, as a preface to the practical procedures which train the practical abilities on each clinical entity in dental medicine